2023
DOI: 10.1093/cercor/bhad349
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb neurogenesis depending on signaling in the subventricular zone

Yali Chen,
Peng Ren,
Xiongjie He
et al.

Abstract: Olfaction is a crucial sense that is essential for the well-being and survival of individuals. Olfactory bulb (OB) is the first olfactory relay station, and its function depends on newly generated neurons from the subventricular zone (SVZ). These newly born neurons constantly migrate through the rostral migratory stream to integrate into existing neural networks within the OB, thereby contributing to olfactory information processing. However, the mechanisms underlying the contribution of SVZ adult neurogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…In contrast, the specificity of the neurogenic effects of STN-DBS with respect to the stimulation target is a strong argument for an indirect stimulation of direct or indirect afferents to the SVZ neurogenic niche as already shown for hippocampal neurogenesis enhanced by electrical stimulation of hippocampal afferents ( Derrick et al, 2000 ; Bruel-Jungerman et al, 2006 ; Toda et al, 2008 ; Encinas et al, 2011 ; Stone et al, 2011 ). However, the corresponding neurogenic network regulating SVZ-OB neurogenesis ( Chen et al, 2023 ) with regard to STN-DBS effects remains to be determined, especially since direct interconnections between the STN and the medial part of the striatum/SVZ are only sparse ( Groenewegen and Berendse, 1990 ; Schmitt et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the specificity of the neurogenic effects of STN-DBS with respect to the stimulation target is a strong argument for an indirect stimulation of direct or indirect afferents to the SVZ neurogenic niche as already shown for hippocampal neurogenesis enhanced by electrical stimulation of hippocampal afferents ( Derrick et al, 2000 ; Bruel-Jungerman et al, 2006 ; Toda et al, 2008 ; Encinas et al, 2011 ; Stone et al, 2011 ). However, the corresponding neurogenic network regulating SVZ-OB neurogenesis ( Chen et al, 2023 ) with regard to STN-DBS effects remains to be determined, especially since direct interconnections between the STN and the medial part of the striatum/SVZ are only sparse ( Groenewegen and Berendse, 1990 ; Schmitt et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampus rather than subventricular is pivotal for mood regulation, which is related to anxiety and depression disorders (Dutheil et al, 2009;Zhao et al, 2018). Recently, Chen et al showed that the olfactory bulb is another neurogenesis niche that relies on the subventricular zone (Chen et al, 2023). Rottstaedt et al revealed that the olfactory bulb volume may be used as a depression biomarker, however, it is insufficient to F I G U R E 2 Role of β-catenin toward psychopathology or psychotherapy depends on its phosphorylation site and body state.…”
Section: β -Catenin and Neurogenesis In Psychiatric Disordersmentioning
confidence: 99%